Growing Healthy During COVID '19. Issue 1 (2nd January 2020) - Elwood, Stephanie M.
ABSTRACT: In Baton Rouge, Louisiana, the Southern University Agricultural Research and Extension Center and community partner nonprofit, Front Yard Bike Shop utilize innovation to continue to reach SNAP-Ed clientele through gardening outreach efforts during the COVID-19 pandemic. Although the stay at home mandate presided by the Governor of Louisiana is in place, we are able to reach students in need through safe, social distancing deliveries. As one of the states with the highest cases of COVID-19, this partnership assures students the opportunity to participate in the therapy of horticulture from their homes, no matter the amount of green space or lack thereof.